Role of Air Transportion in Tourism Development of Karanali Province, Nepal - Chunara, Bhima (Journal of Gurubaba, 2024)
Air transportation is a key driver of tourism development in Karnali Province, where difficult terrain and poor road infrastructure limit accessibility. This study highlights the critical role of air travel in connecting tourists to remote and mountainous areas, making it the most reliable mode of transportation in the region. Surkhet Airport, serving as the central hub, plays a pivotal role in facilitating tourist movement within Karnali. The research confirms a strong, positive relationship between air transport and tourism, revealing that factors such as political stability, economic conditions, environmental seasonality, and travelers' destination choices significantly affect air travel. The study also emphasizes the importance of improving infrastructure and policy support to ensure sustainable tourism growth. Enhancing air transport will not only boost tourism but also contribute to the overall socio-economic development of the province. Continued investment in aviation infrastructure is essential for unlocking Karnali’s full tourism potential and supporting broader national development goals.